What Do Tanzanian Parents Want from Primary Schools—and What Can Be Done about It? - Solomon, Samuel; Zeitlin, Andrew (Research on Improving Systems of Education (RISE), 2019)
Key Points RISE researchers ran a ‘discrete choice’ experiment among parents of school-aged children. They find: • Parents’ choices are driven by proximity and learning quality, with little additional role for class sizes or infrastructure quality. • Parents’ willingness to walk for learning outcomestheir tradeoff between distance and quality—varies widely by region. • Regional variation in willingness to walk for learning is not reflected in the mix of services provided by the school system.
Keywords: _genre:PR-primary_research